Identification of small extracellular RNA fragments of Mycobacterium tuberculosis - Sheldon, Sarah Winter, author; Belisle, John, advisor; Jackson, Mary, committee member; Goodridge, Lawrence, committee member (Colorado State University. Libraries, 2014)
In 2012, the World Health Organization reported 8.6 million estimated incident cases of tuberculosis, 1 million deaths among HIV-negative people, and 0.3 million deaths from HIV-associated tuberculosis. The Stop TB Partnership has a 2015 goal of reducing the 1990 prevalence rates by half. In order to accomplish this goal, there is a large effort to develop new vaccines, diagnostics, treatment, and therapeutics. Understanding how the pathogen, Mycobacterium tuberculosis, interacts with the host is critical to the development of these goals. An emerging area of interest is how host cells respond to bacterial nucleic acids; there are several bacteria that produce nucleic acids that impact pathogenesis through recognition by host pattern recognition receptors. Previous work by Obregón-Henao et al. found that the culture filtrate (CF) of M. tuberculosis was able to induce apoptosis in monocytes, and the material was identified as small stable RNAs. Through cloning, the M. tuberculosis small RNA present in the CF was found to predominantly consist of tRNA and rRNA with lengths between 30 and 70 bases. The goal of this work was to further understand the composition of the small, stable, extracellular RNA of M. tuberculosis. The first step in further elucidating the extracellular RNA population was to develop an RNA isolation method, allowing for the reliable purification of RNA from the CF of M. tuberculosis H37Rv. The method developed previously was not optimized for RNA purification, and a more streamlined method was needed. Available commercial kits did not fit the specific needs of the project as a method was needed to isolate small RNAs from large volumes of CF. The method developed resulted primarily in small RNAs and allowed for isolation of extracellular RNA free of contaminants that could interfere with biological assays, including DNA, protein, LAM, and LPS. The kinetics of RNA release into the CF was examined, comparing the rate of RNA release to that of protein. The RNA and protein were found to have parallel release rates, which could indicate active release rather than passive release of the RNA. Once a reliable RNA isolation method was developed, the composition of the extracellular RNA was interrogated utilizing Next Generation Sequencing as a high-throughput method. A pilot study was developed to determine the optimal concentration of extracellular RNA for sequencing. The Next Generation Sequencing provided a better understanding of the components of the secreted or released RNA. Ribosomal RNA and transfer RNA fragments were found to be present in the extracellular RNA, correlating to what was found by Obergón-Henao et al. A third group of small RNAs were also identified in this study, many of which corresponded to small RNAs previously reported in the literature, however novel small RNA sequences were also identified. The possibility of bias in the sequencing technology was investigated using synthesized tRNA DNA oligonucleotides (stDNA oligos) added at specific concentrations. The quantitation bias study indicated that some bias occurs, although the cause is unknown. All of the stDNA oligos in the sample were identified, giving some confidence in the qualitative nature of this technology. However, based on the possibility of bias, it may be too generous to state that the technology is truly quantitative. Based on these studies, it is possible to say with confidence that what is identified is present, but not that things are not missed. The long-term goals of this work are to fully understand how the extracellular RNA interacts with the host at a molecular level and to understand the mechanism of RNA release. In order to accomplish these goals, it will be necessary to evaluate more M. tuberculosis extracellular RNA using Next Generation Sequencing. A time course study with Next Generation Sequencing should also be done to see if the RNA composition changes over time, as well as for comparison to intracellular small RNAs. It would also be important to develop an assay to confirm fragments found using the Next Generation Sequencer, as well as to evaluate selective release from M. tuberculosis.
Keywords: extracellular RNA; small RNA; next generation sequencing; RNA; Mycobacterium tuberculosis